Amino acids regulate energy utilization through mammalian target of rapamycin complex 1 and adenosine monophosphate activated protein kinase pathway in porcine enterocytes - Xiao, Hao (Anim Nutr, 2020)
As major fuels for the small intestinal mucosa, dietary amino acids (AA) are catabolized in the mitochondria and serve as sources of energy production. The present study was conducted to investigate AA metabolism that supply cell energy and the underlying signaling pathways in porcine enterocytes. Intestinal porcine epithelial cells (IPEC-J2) were treated with different concentrations of AA, inhibitor, or agonist of mammalian target of rapamycin complex 1 (mTORC1) and adenosine monophosphate activated protein kinase (AMPK), and mitochondrial respiration was monitored. The results showed that AA treatments resulted in enhanced mitochondrial respiration, increased intracellular content of pyruvic acid and lactic acid, and increased hormone-sensitive lipase mRNA expression. Meanwhile, decreased citrate synthase, isocitrate dehydrogenase alpha, and carnitine palmitoyltransferase 1 mRNA expression were also observed. We found that AA treatments increased the protein levels of phosphorylated mammalian target of rapamycin (p-mTOR), phosphorylated-p70 ribosomal protein S6 kinase, and phosphorylated-4E-binding protein 1. What is more, the protein levels of phosphorylated AMPK α (p-AMPKα) and nicotinamide adenine dinucleotide (NAD)-dependent protein deacetylase sirtuin-1 (SIRT1) were decreased by AA treatments in a time depending manner. Mitochondrial bioenergetics and the production of tricarboxylic acid cycle intermediates were decreased upon inhibition of mTORC1 or AMPK. Moreover, AMPK activation could up-regulate the mRNA expressions of inhibitor of nuclear factor kappa-B kinase subunit beta (Ikbkβ), integrin-linked protein kinase (ILK), unconventional myosin-Ic (Myo1c), ribosomal protein S6 kinase beta-2 (RPS6Kβ2), and vascular endothelial growth factor (VEGF)-β, which are downstream effectors of mammalian target of rapamycin (mTOR). The mRNA expressions of phosphatidylinositol 4,5-bisphosphate 3-kinase catalytic subunit delta isoform (PIK3CD) and 5′-AMP-activated protein kinase subunit gamma-1 (PRKAG1), which are upstream regulators of mTOR, were also up-regulated by AMPK activation. On the other hand, AMPK activation also down-regulated FK506-binding protein 1A (FKBP1A), serine/threonine-protein phosphatase 2A 55 kDa regulatory subunit B beta isoform, phosphatase and tensin homolog (PTEN), and unc-51 like autophagy activating kinase 1 (Ulk1), which are up-stream regulators of mTORC1. Taken together, these data indicated that AA regulated cellular energy metabolism through mTOR and AMPK pathway in porcine enterocytes. These results demonstrated interactions of AMPK and mTORC1 pathways in AA catabolism and energy metabolism in intestinal mucosa cells of piglets, and also provided reference for using AA to remedy human intestinal diseases.